Do Common Stocks Have Perfect Substitutes? Product Market Competition and the Elasticity of Demand for Stocks - Ahern, Kenneth R. (The Review of Economics and Statistics, 2014)
Though common stocks are one of the most important assets in an economy, little is known about their demand curves. I estimate demand curves for 144 NYSE stocks using a unique data set of all orders, including off-equilibrium orders, during three months in 1990 and 1991. Connecting asset pricing with industrial organization, I find that stocks of firms in less competitive industries are more elastic because they have closer substitutes than stocks in more competitive industries. Tests that exploit the 1991 Gulf War shock and S&P 500 Index additions confirm these results.